(untitled) (American Journal of Islam and Society, 2014)
Index Islamicus, begun in 1906, is a database of bibliographic information of publications in all areas of studies connected with the Islamic world. Since that time, interest in Islamic art and architecture has surged from specialists to many scholars, students, and general interest worldwide. The recent and updated supplements Bibliography of Art and Architecture in the Islamic World, edited by Susan Sinclair, who was assisted by Heather Bleaney and Pablo Garcia Suarez, fills a serious void by listing the materials from 1906 to 2011. Sinclair, an independent scholar with a Ph.D. from the University of London’s Courtauld Institute of Art, is currently researching material in the medievalArab world and has served as the co-editor of the Index Islamicus since 2007. With the support of the university’s renowned School of Oriental and African Studies, she was able to comb the archives of the United Kingdom’s leading institutions, including the National Art Library in London, the British Library, the library of the Warburg Institute, the Cambridge University Library, and the University of Oxford libraries, as well as important collections located in Spain (e.g., the Biblioteca Nacional de España, the Biblioteca Islámica, and the libraries of Consejo Superior de Investigaciones Cientificas). The compilation of resources from these vast collections as well as the material available online has brought this bibliographic collection to a new level. At first glance, the material may seem to be no more than a listing of sources on the subject, with no “content” per se to read. However, the value of such texts and of this set in particular is that the bibliographic listings are grouped by type and subtypes, which enable researchers in particular areas to access a wealth of information not necessarily accessible by other search engines or mechanisms ...